2009
DOI: 10.3138/jvme.36.3.284
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of Personality and Gender at the Louisiana State University School of Veterinary Medicine

Abstract: The goals of this study were to explore the Myers-Briggs Type Indicator profile and gender differences of Louisiana State University veterinary students. A 12-year composite sample (N = 935) revealed that the personality profile was different from the published US population norm, but similar to the bimodal ESTJ-ISTJ profile found in Louisiana medical students. Significant gender differences were found among six of the 16 types. A 12-year trend analysis revealed a significant shift away from the prototypical E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
1
8
3
Order By: Relevance
“…Findings from our study further suggest that there are no preferences for a specific personality type within the student population admitted to the UCDSVM program. These results differ from a previously published study that reported on MBTI personality profiles of students admitted to Louisiana State University, School of Veterinary Medicine from 1996-2007 18 . This 12-year composite descriptive study reported that the personality profile was different from the United States population norm, but similar to the bimodal ESTJ-ISTJ reported in medical students 18 .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Findings from our study further suggest that there are no preferences for a specific personality type within the student population admitted to the UCDSVM program. These results differ from a previously published study that reported on MBTI personality profiles of students admitted to Louisiana State University, School of Veterinary Medicine from 1996-2007 18 . This 12-year composite descriptive study reported that the personality profile was different from the United States population norm, but similar to the bimodal ESTJ-ISTJ reported in medical students 18 .…”
Section: Discussioncontrasting
confidence: 99%
“…These results differ from a previously published study that reported on MBTI personality profiles of students admitted to Louisiana State University, School of Veterinary Medicine from 1996-2007 18 . This 12-year composite descriptive study reported that the personality profile was different from the United States population norm, but similar to the bimodal ESTJ-ISTJ reported in medical students 18 . A 12-year trend analysis revealed a significant shift away from the prototypical ESTJ-ISTJ profile, culminating in a discernible profile for both males and females in the last four years of the study 18 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The Class of 2018 had a mean age of 23.1 years (SD 6 2.6), mean GPA of 3.80 (SD 6 0.14), and mean GRE score of 306.7 (SD 6 8.07), and included 20 males and 67 females upon enrollment within the curriculum. Data regarding gender and Meyer-Briggs personality types within the LSU SVM student cohort from 1996 to 2007 has been previously published (Johnson et al, 2009). A significant response was obtained from the incoming Class of 2018.…”
Section: Participant Selection and Study Populationmentioning
confidence: 99%